Peningkatan Literasi Informasi Bagi Perempuan Indonesia Untuk Melawan Hoax Terkait Covid-19 - Liliana, Dewi Yanti; Andryani, Nur Afny Catur; Sukesi, Keppi (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2022)
Indonesia is the fourth largest populated country in the world. In this country, information can easily spread among people on the internet, whether it is valid information or a false one. Although there is a specific law about information and electronic transaction, people still produce and distribute information without the awareness of the risk. Spreading fake news, especially related to the Covid-19 issue resulted in excessive public reaction or panic because people tend to spread disinformation widely on social media. This has the amplification effect of fears caused by uncontrolled information. Covid-19 fake news in Indonesia has spread out significantly because people are reluctant to read, and most people have low information literacy. The activity aimed to prevent the spread of disruptive information in Indonesia. The activities applied the Penta-helix approach which collaborates several elements: the women's community, communication media, academician, and governments in overcoming disruptive information. 37 participants were from gender study centers across Indonesia. The results are virtual workshops and implementation activities on information literacy. Key persons from each women's study center in all regions of Indonesia attended virtual workshops to strengthen their information literacy skills. Having information-literate key persons, it is proved that the spreading of hoaxes can be reduced. This will support the community in Indonesia to be smarter and wiser in coping with Covid-19 related information. The participants hope that activities to increase information literacy for the Indonesian people can be sustained so that an information-smart society is realized in everyday life.